Application of the Concept of Linear Equation Systems in Balancing Chemical Reaction Equations - Johar, Dwindi Agryanti (International Journal of Global Operations Research, 2020)
This study discusses the equalization of chemical reactions using a system of linear equations with the Gaussian and Gauss-Jordan elimination. The results show that there is a contradiction in the existing methods for balancing chemical reactions. This study also aims to criticize several studies that say that the equalization of the reaction coefficient can use a system of linear equations. In this paper, the chemical equations were balanced by representing the chemical equation into systems of linear equations. Particularly, the Gauss and Gauss-Jordan elimination methods were used to solve the mathematical problem with this method, it was possible to handle any chemical reaction with given reactants and products.